Beauveria Bassiana (Balsamo) Vuillemin: A Successful Biopesticide Against Key Pest Helicoverpa Armigera (Hubner) - ARTI PRASAD; NILOFER SYED; SUJOITA PUROHIT (International Journal of Pharma and Bio Sciences, 2010)
Helicoverpa armigera (Hubner) is an important pest of many economically important crops in Indian subcontinent. Larvae destroy both foliage and fruits of plants. Rapid development of resistance to insecticides has made this insect to acquire status of a key pest.The present study is an attempt to control the pest population of Helicoverpa armigera (Hubner) with an ecosafe entomopathogen Beauveria bassiana (Balsamo) When four different concentrations (0.1,0.125, 0.2 and 0.25ml x108 spores/ml) were sprayed topically against most damaging IVth instar larvae of Helicoverpa armigera (Hubner), a dose dependent mortality was observed that went up to 76.7 percent with highest dose of 0.25ml x108 spores/ml. Dunett test revealed percent mortality significant at 1 and 5 percent level with different doses. Mortality starts after two to three days of treatment and larval death were generally through various morphological deformities in body parts. The treated larvae died mainly due to spread of fungal infections into different body parts. Severity of infection was evident by development of abnormal body parts, fragile skin, entire body covered by fungal mycelia and formation of intermediate stages indicating that chitin is the main target of fungal attack. Auto spread of infection in nearby areas quickly again supplemented the efficient control of pest in one spray.